Dampak Kebijakan Moneter terhadap Pertumbuhan Ekonomi Daerah - Ma'rifin Sugeha, Abdi; Sudirman (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Monetary policy plays a crucial role in promoting regional economic growth, particularly in a country as diverse as Indonesia. This study examines the impact of monetary interventions on the economic development of various provinces, considering the structural economic differences across regions. The research uses a quantitative comparative approach, analyzing data from 10 provinces with the highest economic contributions during the 2015-2023 period. The findings reveal that regions with more diversified economies, such as Jakarta, West Java, and East Java, exhibit a quicker and more pronounced response to monetary policy changes, primarily due to their advanced industrial sectors. In contrast, provinces reliant on natural resources, such as East Kalimantan and Riau, show slower and more complex responses, influenced by global commodity price fluctuations. Additionally, factors such as infrastructure connectivity, human capital, and external global influences significantly shape the transmission of monetary policy in regional economies. The study highlights the importance of tailoring monetary interventions to regional economic characteristics to ensure effective and equitable growth. The COVID-19 pandemic further emphasized the need for economic diversification to mitigate external shocks. The results contribute valuable insights into the relationship between monetary policy and regional economic growth in Indonesia, offering practical recommendations for policy makers.